Justiça como Equidade : uma concepção política de justiça em Rawls - Nüske, Ricardo (2020)
The present study discusses the theory of justice as equity through a political conception of justice in Rawls. Starting from the central idea of a society as an equitable system of social cooperation over time, between free and equal people, the work presents the fundamental bases of the theory of justice. With the specialization of the theory of justice, and from the core organizing idea of an equitable system of social cooperation, the proposed society evolves into a well-ordered society, in other words, governed by a political conception of justice. From a purely hypothetical representation procedure called the initial position, replacing the idea of a social pact, we have the choice of a political conception of justice and of the principles that will specify the levels of social cooperation to be adopted. With the reformulation of Justice as Equity, the principles of justice were adequate in their original wording. During this research, the concepts of reflective balance and overlapping consensus, adopted by Rawls as an instrument for accommodating the comprehensive doctrines existing in modern democratic society, are also addressed. Finally, the question of the application of the principles of justice is approached, starting with the approach of the phases of its application in terms proposed by the philosopher in his work entitled Theory of Justice as Equity. An approach to the conception of principles according to the dictates the Brazilian Constitution of 1988 is also developed, including the Supreme Court judgments. In order to consolidate the issue, the focus is on the judicialization of politics with the possibility of judicializing the control of the application and execution of public policies in the judicial sphere. Lastly, a reflexive analysis is made on the decision that recognized the constitutionality of the application of the quota system for the selection of candidates for vacancies in public universities in the light of the principles of justice.